The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.03.31.018895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of training-induced sarcomerogenesis on the history dependence of force

Abstract: 50The increase or decrease in isometric force following active muscle lengthening or shortening, 51 relative to a reference isometric contraction at the same muscle length and level of activation, are 52 referred to as residual force enhancement (rFE) and residual force depression (rFD), respectively. 53The purpose of these experiments was to gain further mechanistic insight into the trainability of 54 rFE and rFD, on the basis of serial sarcomere number (SSN) alterations to length-dependent 55properties. Maxi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 76 publications
1
17
1
Order By: Relevance
“…Similarly to Blazevich et al (2003) , our results show increases in VL Lf following PLT; this phenomenon is expected to reflect an increase in the number of sarcomeres in series, and thus in maximum shortening velocity ( Bodine et al, 1982 ). Animal studies have shown that sarcomere addition can occur already after 5, 10, and 28 days in response to training modalities involving muscle lengthening ( Lynn et al, 1998 ; Butterfield et al, 2005 ; Chen et al, 2020 ). However, recent studies in intact whole mice muscle have described some variability in sarcomere length along different muscle regions ( Moo et al, 2016 ), which become even more non-uniform upon activation ( Moo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Blazevich et al (2003) , our results show increases in VL Lf following PLT; this phenomenon is expected to reflect an increase in the number of sarcomeres in series, and thus in maximum shortening velocity ( Bodine et al, 1982 ). Animal studies have shown that sarcomere addition can occur already after 5, 10, and 28 days in response to training modalities involving muscle lengthening ( Lynn et al, 1998 ; Butterfield et al, 2005 ; Chen et al, 2020 ). However, recent studies in intact whole mice muscle have described some variability in sarcomere length along different muscle regions ( Moo et al, 2016 ), which become even more non-uniform upon activation ( Moo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the anti-gravity plantarflexors (including SOL) and knee extensors (including VI) are loaded primarily eccentrically during DH running and concentrically during UH running (Margaria, 1968;Armstrong et al, 1983;Butterfield et al, 2005;Maeo et al, 2017). Separate work on the animals tested in the current study (Chen et al, 2020) demonstrated that the EDL had a greater number of sarcomeres in series in both DH and UH training groups compared to the sedentary control group, which may suggest that the EDL performed meaningful eccentric contractions during both DH and UH running.…”
Section: Discussionmentioning
confidence: 51%
“…At the start of each training session, rats started at a walking speed of 10 m/min, which was gradually increased to 16 m/min, at a rate of 1 m/min. Each training session was delivered in a series of 5 min bouts (i.e., 3 on day 1 and 7 on days 5 to the end of the 4 week period) with 2 min or rest between each bout (Chen et al, 2020).…”
Section: Training Protocolmentioning
confidence: 99%
“…Furthermore, running on many consecutive days may minimize time for recovery and hence remodelling between exercise bouts (Hyldahl and Hubal, 2014). This distinction in training stimuli was offered previously as explanation for observations of only small adaptations in rat soleus SSN and mechanical function following downhill running training (Chen et al, 2020). Larger magnitude changes in muscle architecture and strength in animals following 3 days/week training programs support this perspective as well (Butterfield and Herzog, 2006;Ochi et al, 2007;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 74%
“…They completed 3 bouts on the first day and increased by 2 bouts/day up to the 7-bout target (35 minutes total) on the third day of training, which persisted for the remainder of the training period. Rats began each training session at a speed of 10 m/min, which was increased by 1 m/min up to the 16 m/min target (Chen et al, 2020). Progressive loading was employed by adding weight equivalent to 5% of the rat's body mass during the first week, 10% in the second week, 15% in the third week, and 15% readjusted to the new body mass in the fourth week.…”
Section: Methodsmentioning
confidence: 99%